Sexy Blake
XII, 260 p.
Keywords: This book lays bare numerous sexy Blakes, arguing for both chastity and pornography, violence and domination as well as desire and redemption, and also journeying in the realms of conceptual sex and conceptual art. Fierce tussles over the body in, and the body of, the poet-artist's work celebrate Blakean attractions and repulsions.